Studi Perbandingan Kedudukan dan Kewenangan Lembaga Tuha Peut Aceh dan Lembaga Kerapatan Adat Nagari Sumatera Barat - Ali Mahyu K. Mahyu Ali; Putri Kemala Sari Kemala Sari; Apri Rotin Djusfi rotin Djusfi; Basri Basri (Prodi Ilmu Hukum, Universitas Teuku Umar, 2021)
The existence of Indonesia as a form of unitary state has recognized and respected customary law community units and their traditional rights as long as they are still alive and in accordance with the development of society. One of them is regarding the specificity of customary institutions in the province that have certain and special powers such as the Tuha Peut Aceh institution and the West Sumatran Nagari Customary Council (KAN), this study will examine the similarities and differences in the authority of the two traditional institutions in the area. along with the position in the institutional structure of government in the village. This study aims to examine the position of Aceh's Tuha Peut Institution and West Sumatra's Nagari Adat Density Institution and to describe the differences and similarities in authority between the two institutions. The research method uses normative research or library research with a statutory approach and a comparative approach. The results of the study show that the authority for formulating village budgets, formulating village regulations, as well as supervision carried out by the two traditional institutions on the village government will have a positive impact on everyone, where any legal problems that can still be resolved in traditional institutions can still use traditional institutions. existing in an area.